Distribution and characteristics of amphibole asbestos fibres, measured with the light microscope, in the left lung of an insulation worker. Issue 1 (February 1983) - Morgan, A; Holmes, A
Abstract : Concentrations of uncoated and coated amphibole fibres were measured postmortem in samples taken from the periphery of both upper and lower lobes of the left lung of an insulation worker. Similar measurements were made on a more limited range of samples from elsewhere in the lung and on a hilar lymph node. The mean concentration of uncoated fibres in the upper lobe was twice that in the lower. Significant differences were observed in the mean concentration of uncoated fibres in different regions of the periphery, the diaphragmatic region having the lowest value. Variations in the concentrations of both uncoated and coated fibres in the costal region of the lower lobe may have been related to the effect of rib structures on ventilation. Concentrations of fibrous and non-fibrous dust were well correlated in the peripheral samples. The length distributions of uncoated and coated fibres were also measured and differences detected in fibres from the various regions of the lung. This work emphasises the care required in sampling lung tissue in order to obtain representative material for the determination of fibre concentration.